SAT0196 Dekavil (F8-IL10), A Novel Therapeutic Approach for Rheumatoid Arthritis: Ongoing Phase IB Clinical Trial Results. (9th June 2015) - Galeazzi, M.; Sebastiani, G.D.; Bazzichi, L.; Garcia Gonzalez, E.; Ravenni, N.; Giovannoni, L.; Wilton, J.; Selvi, E.; Bardelli, M.; Baldi, C.; Iuliano, A.; Minisola, G.; et al.
Abstract : Background: F8-IL10 (Dekavil) is a fully human immunocytokine, composed of the antibody fragment F8, specific to the extradomain A of fibronectin (EDA-FN), fused to the anti-inflammatory cytokine interleukin-10 (IL-10) [1, 2]. F8-IL10 is currently being investigated as a new therapeutic strategy targeting the inflamed tissues in rheumatoid arthritis (RA). Objectives: To determine the safety and tolerability of Dekavil when administered in combination with methotrexate (MTX) to patients suffering from RA who had failed at least one anti-TNFα drug therapy. To give a preliminary evaluation of the efficacy of Dekavil when administered in combination with MTX. Methods: A Phase Ib non-placebo controlled clinical trial is currently ongoing in order to establish the maximum tolerated dose (MTD) of Dekavil when administered in combination with MTX. Cohorts of 3-6 patients are treated with escalating doses of Dekavil (6, 15, 30, 60, 110, 160, 210, 300, 450 and 600 μg/kg) in combination with a fixed dose of MTX. Dekavil is administered by subcutaneous injection once a week for a maximum of 8 weeks. Results: As of today, the first eight cohorts of the study have been completed (dose levels from 6 to 300 μg/kg). Twenty-six patients are evaluable for safety. No dose limiting toxicities nor serious adverse events have been recorded. No MTD has yet been reached; the dose level of 450 μg/kg is currently ongoing. Mild injection site reaction has been reported in 54% of patients. Regarding systemic adverse reactions, one case of progressive anemia was reported in one patient treated at 160 μg/kg. All adverse reactions resolved after the end of treatment with minor or no therapeutic interventions. A therapeutic benefit of Dekavil, in terms of ACR response, has been recorded in the treated patients, even in subjects treated with low drug dosages. To date, 25 patients are evaluable for efficacy. Among this population, ACR20, 50 and 70 responses were achieved by 60%, 32% and 16% of patients, respectively. In addition, two patients treated at 30 μg/kg and 60 μg/kg dose levels achieved a long-lasting remission. Conclusions: The promising safety profile, together with the preliminary efficacy responses in this non-placebo controlled trial led to the start of a Phase II placebo-controlled trial within the same patient population to verify the efficacy of low dosages of Dekavil in combination with MTX. The currently available data suggest the targeted delivery of IL-10 to the sites of inflammation is a promising therapeutic approach for RA. References: K. Schwager et al. (2009) Arthritis Res. Ther., 11, R142 F. Doll et al (2013) Arthritis Res. Ther., 15, R138 Disclosure of Interest: M. Galeazzi: None declared, G. Sebastiani: None declared, L. Bazzichi: None declared, E. Garcia Gonzalez Consultant for: Philogen, N. Ravenni Employee of: Philogen, L. Giovannoni Employee of: Philogen, J. Wilton Consultant for: Philogen, E. Selvi: None declared, M. Bardelli: None declared, C. Baldi: None declared, A. Iuliano: None declared, G. Minisola: None declared, R. Caporali: None declared, S. Bombardieri: None declared, D. Neri Shareholder of: Philogen